The hidden side of migration: Understanding sexuality as an aspiration to migrate - Usta, Dilvin Dilara; Ozbilgin, Mustafa F. (Frontiers in Sociology, 2023)
Sexuality is an understated yet increasingly important motive for migration. Motivation to migrate is often viewed from a polarised lens, either as the pursuit of economic security or as a desire to access to human rights, on which social policy on migration has been predicated. We introduce the notion of the toxic triangle to account for contexts that prove hostile to freedom of sexuality and trigger individuals to migrate. Drawing on insights from 25 interviews, we demonstrate how sexuality remains a silent yet significant contributor to individuals’ decisions to migrate from an adversarial context. We illustrate how the participants fall into four archetypes of dreamers, climbers, escapists, and seekers, based on their endowments and experiences of sexuality and gender identity as salient sources of their motivation to migrate. Focusing on the hidden side of Turkish migration to the UK offers insights into how the pursuit of freedom of sexuality in terms of safety and security shapes motivations and experiences of migration across two cultures.